A Theory of Economic Disintegration - Eckhard Janeba; Karl Schulz (ZBW - Leibniz Information Centre for Economics, 2020)
We develop a theory of economic disintegration that features both endogenously formed tax and trade policies. We show very generally that the economic disintegration of a country from an economic union leads to a deeper integration of international trade institutions. Moreover, we set up a multi-country, multi-sector general equilibrium trade model with internationally mobile firms. We address the key dimensions of economic disintegration, such as tariffs, non-tariff barriers, the harmonization of production standards and regulations, as well as household migration and analyze their effects on the domestic tax policies of asymmetric countries.
Keywords: F13; F15; F22; F53; H25; H73; 330; Trade Policy; Tax/Subsidy Competition; Oligopolistic Markets; Economic Integration